Meningkatkan Hasil Belajar Siswa Mata Pelajaran Tematik Melalui Metode Index Card Match - Nur Hakim (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2018)
Learning outcomes is an effort in the application of Index Card Match method to improve the learning outcomes of thematic subjects theme 6 my dreams,subtema 3 Active Trying to Achieve Ideals, learning 2 in grade IV B MI Tarbiyatut Tholabah Kranji Paciran Lamongan Lesson 2017-2018. The formulation of this research is whether the use of Index Card Match method can improve students' learning outcomes of thematic subjects theme 6 subtema 3 learning 2 in class IV B in MI Tarbiyatut Tholabah Kranji Paciran Lamongan 2017-2018 school year? Classroom action research is carried out through three cycles, namely cycle I, cycle II, and cycle III, each cycle there are four stages: 1) Planning, 2) Acting, 3) Observing, and 4) Reflecting. The data collection methods used include multiple choice test, observation, and documentation. The results of this study indicate that the application of Index Card Match method can improve the learning outcomes Thematic theme 6 My dreams, subtema 3 Active Trying to Achieve Ideals, learning 2. The results achieved based on the cognitive domain through the application of Index Card Match method on subjects Thematic themes 6 subtema 3 lesson 2 in MI Tarbiyatut Tholabah experienced a significant increase. This is seen in the acquisition of learning outcomes that teachers give each end of the cycle, that the average of student learning outcomes on the theme Thematic theme 6 subtema 3 learning 2 in the first cycle of 63.93 with 50% completeness percentage, on the second cycle average student learning outcomes increased to 69.46 with the percentage of mastery 67.86% and the average in the third cycle increased to 79.64 with the percentage of 92.86% mastery. The results of this study indicate that student learning outcomes by applying Index Card Match method can improve student learning outcomes.